Human Anti-Als3p Antibodies Are Surrogate Markers of NDV-3A Vaccine Efficacy Against Recurrent Vulvovaginal Candidiasis - Uppuluri, Priya; Singh, Shakti; Alqarihi, Abdullah; Schmidt, Clint S.; Hennessey, John P.; Yeaman, Michael R.; Filler, Scott G.; Edwards, John E.; Ibrahim, Ashraf S. (Frontiers in Immunology, 2018)
A Phase 1b/2a clinical trial of NDV-3A vaccine containing a Candida albicans recombinant Als3 protein protected women <40 years old from recurrent vulvovaginal candidiasis (RVVC). We investigated the potential use of anti-Als3p sera as surrogate marker of NDV-3A efficacy. Pre- and post-vaccination sera from subjects who experienced recurrence of VVC (R) versus those who were recurrence-free (non-recurrent, NR) were evaluated. Anti-Als3p antisera obtained were evaluated for; 1) titer and subclass profile; 2) their ability to influence C. albicans virulence traits including hyphal elongation, adherence to plastic, invasion of vaginal epithelial cells, biofilm formation on plastic and catheter material, and susceptibility to neutrophil killing in vitro. Serum IgG titers in NR patients were consistently higher than in R patients, particularly for anti-Als3 subclass IgG2. Sera from vaccinated NR patients reduced hyphal elongation, adhesion to plastic, invasion of vaginal epithelial cells and biofilm formation significantly more than pre-immune sera, or sera from R- or placebo-group subjects. Pre-adsorption of sera with C. albicans germ tubes eliminated these effects, while heat inactivation did not. Finally, sera from NR subjects enhanced neutrophil-mediated killing of C. albicans relative to pre-immune sera or sera from R patients. Our results suggest that higher Als3p antibody titers are associated with protection from RVVC, attenuate C. albicans virulence and augment immune clearance of the fungus in vitro. Thus, Als3p serum IgG antibodies are likely useful markers of efficacy in RVVC patients vaccinated with NDV-3A.